Pathologies Underlying Longitudinal Cognitive Decline in the Oldest Old. (October 2018) - Nguyen, Madeline T.; Mattek, Nora; Woltjer, Randy; Howieson, Diane; Silbert, Lisa; Hofer, Scott; Kaye, Jeffrey; Dodge, Hiroko; Erten-Lyons, Deniz
Abstract : Background: Understanding contributions of different brain pathologies to domain-specific cognitive trajectories in the oldest old is crucial to guide future intervention studies. Methods: Two-hundred-twenty Oregon Alzheimer's Disease Center research participants who were cognitively intact at entry were followed on average for 7.3 years with annual neuropsychological testing until death (mean age, 93.7 y) and autopsy. Mixed effects models examined the relationship between trajectories in memory, verbal fluency, and mini-mental state examination (MMSE) and pathology (neurofibrillary tangles, neuritic plaques, gross infarcts, hippocampal sclerosis, Lewy bodies, APOE genotype, age at death, and years of education). The association between the MMSE trajectory and pathologic variables were examined using a Poisson model with MMSE errors as outcomes given the nonlinear distribution of MMSE scores. Results: Memory trajectory was associated with the APOε4 allele ( P =0.006). Verbal fluency trajectory was associated with gross infarcts ( P =0.008). MMSE trajectory was associated with high Braak scores ( P =0.03), gross infarcts ( P <0.0001), hippocampal sclerosis ( P =0.003), moderate neuritic plaques ( P =0.04), and the APOε4 allele ( P =0.02). Conclusions: The association between trajectory of decline in global cognitive scores and multiple brain pathologies highlights the importance of accounting for comorbid pathologies in therapeutic trials aimed at one specific pathology in the oldest old. Only the APOε4 allele showed an association with memory decline, despite accounting for Alzheimer's disease pathology, suggesting that APOE may be involved in mechanisms beyond amyloid metabolism in its role in memory. Further studies are needed to examine the role of APOE in brain aging.